Prognostic Utility of the Modified Systemic Inflammation Score for Patients Undergoing Oral Cavity Cancer Surgery - Ku-Hao Fang; Sheng-Wei Lo; Adarsh Kudva; Andrea De Vito; Yuan-Hsiung Tsai; Cheng-Ming Hsu; Geng-He Chang; Ethan I. Huang; Ming-Shao Tsai; Chia-Hsuan Lai; Ming-Hsien Tsai; Chun-Ta Liao; et al. (Diagnostics)
Background/Objectives: Chronic inflammation significantly contributes to human malignancies. We investigated the prognostic significance of the preoperative modified systemic inflammation score (mSIS) in patients with primary oral cavity squamous cell carcinoma (OCSCC). Methods: We retrospectively reviewed data from 320 OCSCC patients who underwent curative surgery between 2007 and 2017. Based on preoperative lymphocyte-to-monocyte ratio (LMR) and serum albumin levels, patients were classified into three groups: mSIS = 2 (LMR < 3.4 and albumin < 4.0 g/dL), mSIS = 1 (LMR < 3.4 or albumin < 4.0 g/dL), and mSIS = 0 (LMR ≥ 3.4 and albumin ≥ 4.0 g/dL). We explored the associations between the preoperative mSIS and overall survival (OS) and disease-free survival (DFS). We developed a nomogram based on mSIS for OS prediction. Results: The distribution was mSIS = 0 (n = 197, 61.6%), mSIS = 1 (n = 99, 30.9%), and mSIS = 2 (n = 24, 7.5%). Kaplan–Meier estimated OS and DFS for the mSIS = 0, mSIS = 1, and mSIS = 2 groups demonstrated a sequential decrease (both p < 0.001). The prognostic significance of mSIS was consistent across subgroup analyses. Multivariable analysis revealed that mSIS = 1 and mSIS = 2 were independent negative prognostic indicators. The mSIS-based nomogram effectively predicted OS (concordance index: 0.755). Conclusions: The mSIS reliably predicts OS and DFS in OCSCC patients undergoing surgery, with the nomogram providing individualized OS estimates, enhancing mSIS’s clinical utility.